Composite Inflammatory Indicators as Early Predictor of Intra-abdominal Infections after General Surgery - Song J; Lu Y (Dove Medical Press, 2021)
Jiakun Song, Yurong Lu Emergency Department, Sandun District of Zhejiang Hospital, Hangzhou, Zhejiang, People's Republic of ChinaCorrespondence: Yurong LuEmergency Department, Sandun District of Zhejiang Hospital, 1229 Gudun Road, Xihu District, Hangzhou, Zhejiang 310030, People's Republic of ChinaTel +86-137-0581-4277Email luyurong120@163.comObjective: To identify rapid and accurate early diagnostic indicators for intra-abdominal infection (IAI) after general surgery.Methods: We conducted a retrospective analysis of 3,810 general surgical patients in our hospital from August 2017 to July 2018. The predictive value of PCT, CRP, TNFα, and IL6 on postoperative days (PODs) 1 and 3 and composite indicators for complicated IAIs among surgical patients was clarified.Results: There were 271 patients in the infected group and 614 patients in the uninfected group using IAI diagnostic criteria in this study. CRP, PCT, TNFα, and IL6 in the infected group were significantly higher than the uninfected group on POD1 and POD3. In the infected group, the composition of the four indicators on POD1 (AUC 0.819) and POD3 (AUC 0.848) showed higher predictive efficiency than the individual indicators (AUC 0.670- 0.805).Conclusion: The composite of CRP, PCT, TNFα, and IL6 can be used as a predictor of postoperative abdominal infectious complications with high sensitivity and specificity on POD1 and POD3, which can provide a basis for early diagnosis of postoperative abdominal infectious complications.Keywords: procalcitonin, C-reactive protein, TNFα, IL6, intra-abdominal infection